Effect of folic acid supplementation on cardiovascular outcomes: a systematic review and meta-analysis. - Yu-Hao Zhou; Jian-Yuan Tang; Mei-Jing Wu; Jian Lu; Xin Wei; Ying-Yi Qin; Chao Wang; Jin-Fang Xu; Jia He (PLoS ONE)
Background Folic acid is widely used to lower homocysteine concentrations and prevent adverse cardiovascular outcomes. However, the effect of folic acid on cardiovascular events is not clear at the present time. We carried out a comprehensive systematic review and meta-analysis to assess the effects of folic acid supplementation on cardiovascular outcomes. Methodology and principal findings We systematically searched Medline, EmBase, the Cochrane Central Register of Controlled Trials, reference lists of articles, and proceedings of major meetings for relevant literature. We included randomized placebo-controlled trials that reported on the effects of folic acid on cardiovascular events compared to placebo. Of 1594 identified studies, we included 16 trials reporting data on 44841 patients. These studies reported 8238 major cardiovascular events, 2001 strokes, 2917 myocardial infarctions, and 6314 deaths. Folic acid supplementation as compared to placebo had no effect on major cardiovascular events (RR, 0.98; 95% CI, 0.93-1.04), stroke (RR, 0.89; 95% CI,0.78-1.01), myocardial infarction (RR, 1.00; 95% CI, 0.93-1.07), or deaths from any cause (RR, 1.00;95% CI, 0.96-1.05). Moreover, folic acid as compared to placebo also had no effect on the following secondary outcomes: risk of revascularization (RR, 1.05; 95%CI, 0.95-1.16), acute coronary syndrome (RR, 1.06; 95%CI, 0.97-1.15), cancer (RR, 1.08; 95%CI, 0.98-1.21), vascular death (RR, 0.94; 95%CI,0.88-1.02), or non-vascular death (RR, 1.06; 95%CI, 0.97-1.15). Conclusion/significance Folic acid supplementation does not effect on the incidence of major cardiovascular events, stroke, myocardial infarction or all cause mortality.